ISOLASI, IDENTIFIKASI, DAN SKRINING JAMUR ENDOFIT PENGHASIL AGEN BIOKONTROL DARI TANAMAN DI LAHAN PERTANIAN DAN HUTAN PENUNJANG GUNUNG SALAK - Suciatmih, Suaciatmih; yuliar, Yuliar; Supriyati, D (Jurnal Teknologi Lingkungan, 2011)
Isolation of endophytic fungi was done to find alternative microorganisms as biocontrolÃ‚Â agents against Rhizoctonia solani Kuhn, a soil borne pathogen on many agriculturalcrops. The research objectives were 1) to isolate and identify endophytic fungi colonizeÃ‚Â plants growing on agricultural and Mount Salak supporting forest lands in the VillagesÃ‚Â of Parakan Salak and Cimalati, Sukabumi; and 2) to screen for their biocontrol agentÃ‚Â activity againt R. solani. Diameter of R. solani was measured on day 2 after inoculation,Ã‚Â and its percent inhibition of growth by endophytic fungi is calculated using the formulaÃ‚Â Skidmore & Dickinson (1976). The results indicated that 214 isolates of endophyticÃ‚Â fungi were isolated from 96 plant species that growing in both places. Endophytic fungiÃ‚Â isolated including in the group of Aspergillus, Cladosporium, Colletotrichum, Curvularia,Ã‚Â Drechslera, Fusarium, Guignardia, Mucor, Nigrospora, Paecilomyces, Penicillium,Ã‚Â Pestalotiopsis, Phoma, Phomopsis, Rhizoctonia, and endophytic fungi that have notÃ‚Â been identified. Of the 214 fungal isolates tested, 39 isolates (18.22 %) could inhibitÃ‚Â the growth of R. solani from 10.18 % to 58.99 % with a percent inhibition. The highestÃ‚Â growth inhibition of R. solani were shown respectively by an unidentified fungus isolatedfrom Hyptis capitata Jack (58.99%), Cladosporium sp. isolated from jeruk bali (CitrusÃ‚Â grandis (L.) Osbeck) (55.42%), Pestalotiopsis sp. isolated from pine apple (AnanasÃ‚Â comosus (L.) Merr.) (53.85 %), and Paecilomyces lilacinus (Thom) Samson isolatedÃ‚Â from banyan (Ficus benyamina L.) (51.81%)Ã‚Â